Creative people tend to tell lies, especially in enriched environment - Chan, Shia-Wen; Tan, Wan-Qing; Tan, Chee-Seng (Penerbit Universiti Kebangsaan Malaysia, 2016)
Is dishonesty affected by one’s creativity and environment? Recent studies have documented the effects of creativity and environment on dishonesty respectively. However, little attention has been given to the interaction effect of creativity and environment. Based on past findings, we hypothesized that creative people, compared to their non-creative counterparts, may tell more lies in an enriched (vs. scarce) environment. An experiment was conducted on a sample of 97 undergraduate students to examine the moderation effect of environment on the linkage of creativity and cheating. Participants completed a creativity task and a questionnaire on general knowledge about Malaysia. Two-way ANOVA analysis showed that creative participants, as well as those in the enriched environment, were more likely to tell lies than their counterparts. More importantly, the interaction effect of creativity and environment was statistically significant. Specifically, the creative people were more likely to cheat in the enriched envi-ronment than in the scarce environment. The results not only shed light on the link between creativity and dishonesty but also suggest a new direction for minimizing dishonesty behaviours.